2022
DOI: 10.3389/fenvs.2022.760147
|View full text |Cite
|
Sign up to set email alerts
|

Representation of Drought Events in the United Kingdom: Contrasting 200 years of News Texts and Rainfall Records

Abstract: This paper combines evidence from the analyses of large sets of newspaper material and long-term rainfall records to gain insights into representations of drought events in the United Kingdom, between 1800 and 2014. More specifically, we bring together two different, though complementary, approaches to trace longitudinal patterns in the ways drought events have been measured and perceived, focusing specifically on the duration, spatial extent, and intensity of each event. The power of the combined approach is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Such an absence of media coverage, despite climatic anomalies favourable for drought conditions in our analysis, is interesting because the UKCEH also confirmed the drought-prone conditions in these years with reports of unusual hydrological events published for the years of 2003-2006, 2010-2012. A similar mismatch between media coverage and drought-prone meteorological conditions was also identified by Dayrell et al (2022) who explored the text corpora about droughts over the last 200 years in the UK. Dayrell et al (2022) suggested that such mismatched derived from the newsworthiness of events: even if the meteorological conditions are favourable for droughts, they may not generate media coverage due to the lagging effect of rainfall shortage to newsworthy drought events.…”
Section: How Do Meteorological Conditions Relate To Media Coverage?supporting
confidence: 82%
See 2 more Smart Citations
“…Such an absence of media coverage, despite climatic anomalies favourable for drought conditions in our analysis, is interesting because the UKCEH also confirmed the drought-prone conditions in these years with reports of unusual hydrological events published for the years of 2003-2006, 2010-2012. A similar mismatch between media coverage and drought-prone meteorological conditions was also identified by Dayrell et al (2022) who explored the text corpora about droughts over the last 200 years in the UK. Dayrell et al (2022) suggested that such mismatched derived from the newsworthiness of events: even if the meteorological conditions are favourable for droughts, they may not generate media coverage due to the lagging effect of rainfall shortage to newsworthy drought events.…”
Section: How Do Meteorological Conditions Relate To Media Coverage?supporting
confidence: 82%
“…We then explored how drought in spring 2012 and summer 2022 were presented in media contents performing close reading of newspaper headlines (c.f. Dayrell et al 2022). We also visualized the topic compositions for each month for these two events, to show the prevalence of topics.…”
Section: Close Readingmentioning
confidence: 99%
See 1 more Smart Citation
“…The prolonged period of inhomogeneity in the Manchester and HadNWEP comparison (Figure 4b), marked by statistically significant breakpoints in 1933 and 1948, occurred during a 16-year period of the Whitworth record. Notable droughts were recorded within the UK in both 1933-35 [45,46] and 1946-49 [47]; however, the latter was poorly documented and reported on in the national press because of wartime reporting restrictions, as food rationing was in place. The station metadata provides no information clarifying the source of the detected inconsistency.…”
Section: Identifying Causes Of Statistical Inhomogeneitymentioning
confidence: 99%
“…(2017) also used newspaper collections to verify the occurrence and duration of historical droughts. The utility of newspaper articles as a source of information on drought impacts has also been demonstrated in the UK (e.g., Dayrell et al ., 2022) and elsewhere (e.g., Llasat et al ., 2009; Linés et al ., 2017; Brázdil et al ., 2019).…”
Section: Introductionmentioning
confidence: 95%